IDENTIFIKASI ADVERSE DRUG REACTION (ADR) OBAT ANTI TUBERKULOSIS PADA PASIEN TB DI RSUD PASAR REBO JAKARTA TIMUR - Dini Permata Sari; Julita Silitonga; Farisa Luthfiana; Ria Anggraeni (Universitas Imelda Medan, 2026)
Tuberculosis (TB) remains a major public health problem in Indonesia, ranking second globally in TB burden. Although Anti-Tuberculosis Drugs (ATDs) are effective in curing TB, prolonged treatment and combination regimens may lead to Adverse Drug Reactions (ADRs), potentially affecting patient adherence and treatment outcomes. This study aimed to identify the types of ADRs experienced by TB patients undergoing ATD therapy at Pasar Rebo General Hospital, East Jakarta, and to analyze the relationship between age, gender, and duration of drug use with ADR occurrence. This research employed a descriptive-analytic retrospective design conducted from June to July 2025. A total of 60 adult TB patients receiving first-line ATD therapy (Isoniazid, Rifampicin, Pyrazinamide, and Ethambutol) were included. Data were collected using questionnaires and analyzed using univariate and multivariate statistical methods with SPSS. Causality assessment of ADRs was performed using the Naranjo algorithm. The results showed that 88.33% of patients experienced ADRs. The most frequently reported symptoms were nausea (48.33%), rash/itching (28.33%), and joint pain (26.67%). Most ADRs were categorized as “Probable” based on the Naranjo score. Multivariate analysis revealed that gender was significantly associated with ADR occurrence (p = 0.041), while age and duration of drug use were not statistically significant. In conclusion, ADRs are common among TB patients receiving ATD therapy, with gastrointestinal and dermatological symptoms being the most prevalent. Gender appears to be an important predictor of ADR risk. Therefore, close clinical monitoring and gender-sensitive pharmacovigilance strategies are essential to ensure patient safety, improve adherence, and optimize TB treatment outcomes.